Las TIC’S aplicadas al proceso de enseñanza aprendizaje de los docentes del colegio de bachillerato “ZUMBI” de la parroquia Zumbi, cantón Centinela del Cóndor – provincia de Zamora Chinchipe, periodo 2014– 2015. Propuesta alternativa - León Loja, Cristian José (2016)
The present research: LAS TIC’s APLICADAS AL PROCESO DE ENSEÑANZA APRENDIZAJE DE LOS DOCENTES DEL COLEGIO DE BACHILLERATO “ZUMBI” DE LA PARROQUIA ZUMBI, CANTÓN CENTINELA DEL CÓNDOR - PROVINCIA DE ZAMORA CHINCHIPE, PERIODO 2014 – 2015. PROPUESTA ALTERNATIVA, was carried out according to the provisions of Regulation Academic Board of the National University of Loja. The central problem of the research was: to understand and analyze the current reality of the application of Tic’s in the teaching-learning process by school teachers of Colegio de Bachillerato "Zumbi", the general objective was: To analyze the use of Tic's applied in the teaching-learning process for teachers of Colegio de Bachillerato "Zumbi" to establish alternative proposals. The methodology used for the preparation of this research work were the following methods: scientific, deductive, inductive, descriptive and statistical model, which allowed to achieve the goal proposed efficiently in the following thesis research, in agreement with each phase as is required by scientific research. The techniques and instruments used in this research were: the survey applied to teachers to determine the use of Tic’s in the teaching-learning process, and observation of classroom activities of teachers to verify the application of Tic’s during the process of teaching and learning and teaching practices. According to the results it is concluded that: 58% of teachers surveyed express their knowledge in the use of Tic’s is regular, 23% say it is good, 11% considered their knowledge in Tic’s as poor, while 8% consider it is very good. Likewise, 73% of respondents do not use new technologies to communicate with students, 11%, they said they use new technologies to communicate with students. In addition, 92% of teachers surveyed believe that the importance of Tic’s is highly significant in the classroom to support their teaching and improve the teaching-learning process.